2003
DOI: 10.4489/myco.2003.31.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofCryptococcus neoformansvar.grubii(serotype A) from Pigeon Droppings in Korea

Abstract: Three hundred and sixty five samples of avian droppings, collected from parks and zoo, were investigated for the occurrence of Cryptococcus neoformans in Korea. Thirteen samples were positive for C. neoformans. All isolates were obtained from withered pigeon droppings. Identification and serotyping of isolates were determined by means of serological test and polymerase chain reaction (PCR) fingerprinting. All isolates belonged to C. neoformans var. grubbi (serotype A). KEYWORDS: Cryptococcus neoformans, Pigeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Genetic similarities recently have been shown between isolates from animal sources and human patients in Thailand [ 6 ]. This study strongly confirmed that dried droppings are more likely to contain yeast spores than fresh droppings [ 2 ]. The incidence of C. neoformans in the environment previously has been reported to depend on abiotic components, including the presence of protein, carbohydrate and creatinine, and physical conditions including light, temperature and moisture [ 4 , 15 , 17 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Genetic similarities recently have been shown between isolates from animal sources and human patients in Thailand [ 6 ]. This study strongly confirmed that dried droppings are more likely to contain yeast spores than fresh droppings [ 2 ]. The incidence of C. neoformans in the environment previously has been reported to depend on abiotic components, including the presence of protein, carbohydrate and creatinine, and physical conditions including light, temperature and moisture [ 4 , 15 , 17 ].…”
Section: Discussionsupporting
confidence: 81%
“…Temples and public parks were prioritized areas due to their high density of pigeon flocks that were likely to represent the highest risk of contamination to the public. Overall, the occurrence of C. neoformans (11%) was at a lower percentage than reports for Chiang Mai, Thailand (16.4–45%), Seoul, Korea (25%) and Grand Canary Island (24.45%) [ 2 , 21 , 25 ]. In Bangkok, the distribution was focal, and of the three positive districts, the rate was substantially higher in Nongkhaem (9/16, 56.2%) and Latphrao (7/16, 43.7%) than in Khlongtoei (2/15, 13.3%).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is possible to verify that several studies evidencing the importance of bird dropping as a suitable substrate for the growth of yeasts and filamentous fungi [8][9][10][11][12][13][14][15]. Birds easily conduct the agent in the environment through its feces and become a zoonotic problem due to its proximity with the humans, explained by the fact that it is a peridomestic animal.…”
Section: Introductionmentioning
confidence: 87%
“…However, the molecular epidemiology of the C. neoformans / C. gattii species complex has not been investigated and little is known about the association between HIV infection and cryptococcosis in the Republic of Korea. Only one clinical study (Woo, 2008) and one environmental study (Chee & Lee, 2005) has been conducted, but molecular types of the cryptococcal isolates have not been determined. A study by Woo (2008), which focused only on non‐HIV cryptococcosis cases, indicated that, unlike in China, nearly 60% of the Korean patients had serious underlying conditions.…”
Section: Introductionmentioning
confidence: 99%